Symptom's resolution and growth outcome of children with cow's milk protein allergy consuming two hydrolyzed formulas: A retrospective study in Mexico - Estrada Reyes, Elizabeth; Zepeda Ortega, Benjamín; ten Haaf, Dominique; Kudla, Urszula; Muhardi, Leilani; Hofman, Denise L.; Hageman, Jeske H. J.; Huerta Hernández, Rosa E. (Frontiers in Allergy, 2023)
Background Cow's milk protein allergy (CMPA) is the leading cause of food allergy in infants and young children. An extensively hydrolyzed formula (eHF) is the first choice of dietary management, however, not all of them have similar peptide profiles and degree of hydrolysis. The aim of this retrospective study was to investigate the use of two commercially available infant formulas in the clinical management of CMPA in Mexico in terms of symptoms' resolution and growth trajectories. Methods Medical records of 79 subjects from four sites in Mexico were included to retrospectively evaluate the trajectory of atopic dermatitis, other symptoms of cow's milk protein allergy and growth outcomes. The study formulas were based on hydrolyzed whey protein (eHF-W) and hydrolyzed casein protein (eHF-C). Results Medical records of 79 patients were enrolled, 3 were excluded from analysis based on previous formula consumption. Seventy-six children with confirmed CMPA based on skin prick test and/or serum specific IgE levels were included in the analysis. 82% of patients (n = 65) consumed the eHF-C, reflecting the doctors' preference for formulas with a higher grade of hydrolysis and the high incidence of positive reactions to beta-lactoglobulin amongst subjects. During their first visit to the doctors, 55% of the subjects consuming the casein-based formula and 45% of subjects consuming the whey-based formula presented with mild or moderate dermatological symptoms. Other frequently reported symptoms included respiratory issues, enteropathies and colitis which improved during the consumption of both formulas. All CMPA-related symptoms showed improvement during formula consumption. During the period of retrospective observation, growth significantly improved for both groups. Conclusion Consumption of eHF-C and eHF-W effectively improved symptoms' resolution and growth outcomes among children with CMPA in Mexico. More preference was reported towards eHF-C due to its hydrolysate profile and lack of b-lactoglobulin. Trial registration The study was registered at ClinicalTrials.gov: NCT04596059.